Analysis Of Knowledge, Characteristics, Attitude, And Behavior Of Nurses Regarding The Use Of Ppe (Personal Protection Equipment) In Accordance With Standard Operational Procedure (Sop) In The Inpatient Room Of Royal Prima Medan General Hospital - Rama Atma Negara; Chrismis Novalinda Ginting; Yolanda Eliza Putri; Mangatas Silaen (International Journal of Health and Pharmaceutical (IJHP), 2022)
Personal Protective Equipment (PPE) is special clothing or equipment used for personal protection from infectious materials. Nosocomial infections are a global health problem. One of the most popular nosocomial infections is the case of the Corona-19 virus (COVID). PPE protects healthcare workers from infectious infections and helps prevent cross-contamination with other patients. The purpose of this study was to determine the analysis of knowledge, characteristics, attitudes, and behavior of nurses regarding the use of PPE according to the Standard Operational Procedure (SOP) in the Inpatient Room of the Royal Prima General Hospital, Medan. This type of research is an analytical observational study with a cross-sectional study design. There is a significant relationship between the characteristics, attitudes, and behavior of nurses on the use of PPE (p <0.05).